2012
DOI: 10.1136/bmjopen-2011-000665
|View full text |Cite
|
Sign up to set email alerts
|

CareTrack Australia: assessing the appropriateness of adult healthcare: protocol for a retrospective medical record review

Abstract: IntroductionIn recent years in keeping with international best practice, clinical guidelines for common conditions have been developed, endorsed and disseminated by peak national and professional bodies. Yet evidence suggests that there remain considerable gaps between the care that is regarded as appropriate by such guidelines and the care received by patients. With an ageing population and increasing treatment options and expectations, healthcare is likely to become unaffordable unless more appropriate care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
(12 reference statements)
0
45
0
Order By: Relevance
“…A sample designed to be representative of the adult Australian population was randomly selected from a phone directory (the Telstra White Pages) from defined regions within South Australia and New South Wales 12,13 . One adult was randomly selected from each household and recruited via the telephone.…”
Section: Recruitment Of Participants and Healthcare Providersmentioning
confidence: 99%
See 2 more Smart Citations
“…A sample designed to be representative of the adult Australian population was randomly selected from a phone directory (the Telstra White Pages) from defined regions within South Australia and New South Wales 12,13 . One adult was randomly selected from each household and recruited via the telephone.…”
Section: Recruitment Of Participants and Healthcare Providersmentioning
confidence: 99%
“…A training manual provided inclusion and exclusion criteria and instructions for scoring indicators. Estimates for compliance were measured as the percentage of eligible encounters 12 for the SSI indicators that were answered 'yes'. The inclusion criteria for the indicators were specific to particular types of surgery (e.g.…”
Section: Review Of Medical Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…A seminal study in the United States showed that American adults received “recommended care” only 55% of the time in the years 1999–2000 1 . Estimates of “appropriate care” — defined here as care in line with evidence‐based or consensus‐based guidelines 2 — are limited in most countries, including Australia, to small groups of conditions, often in particular settings 3 , 4…”
mentioning
confidence: 99%
“…In addition, our method for developing the indicators systematically combined the available evidence base with the opinion of clinical experts to develop indicators that are both face and content valid 19. The modified RAND method used in our study has been used in indicator development studies previously 18 45. A recent Australian study used this method to validate 657 indicators of healthcare appropriateness 16…”
Section: Discussionmentioning
confidence: 99%